Ferritic stainless steel and method for producing the same
Patent Information
- Application Number
- JP2023128813
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-20
Smart Images

Figure 2025024596000001 
Figure 2025024596000002 
Figure 2025024596000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a ferritic stainless steel material and a method for producing the same. [Background technology]
[0002] Ferritic stainless steel materials are inexpensive because they contain no Ni or only a small amount of Ni, but their applications are sometimes limited because they are inferior in corrosion resistance and workability to austenitic stainless steel materials.
[0003] In recent years, the expansion of applications of ferritic stainless steel materials has led to a demand for improved corrosion resistance of ferritic stainless steel materials. In particular, in applications such as building panels and piping, which may be used in outdoor environments (e.g., outdoor corrosive environments such as salt damage environments), weather resistance is required. Examples of weather resistance include the inhibition of rusting in outdoor environments and the inhibition of holes caused by corrosion. In addition, since ferritic stainless steel materials are processed into a predetermined product shape, they are also required to be able to be processed by bending, pressing, and other processes, that is, to have processability.
[0004] As a technique for improving the corrosion resistance of ferritic stainless steel materials, a method of adding alloy elements such as Cr and Mo is known. However, in ferritic stainless steel materials, once corrosion (pitting corrosion) has occurred, it progresses faster than in austenitic stainless steel materials, so in order to slow down the rate of corrosion progression, it is necessary to add large amounts of Cr and Mo. However, adding large amounts of Cr and Mo would undermine the advantage of ferritic stainless steel materials, that is, their low cost.
[0005] Furthermore, as a technique for improving the corrosion resistance of ferritic stainless steel materials (raw materials), a method for controlling the amount of added Si is known (for example, Patent Documents 1 to 3). However, the method of controlling the amount of Si added does not improve weather resistance. In fact, the addition of Si is effective in improving corrosion resistance in neutral environments, but has almost no effect in suppressing the progress of corrosion in outdoor environments (especially in low pH environments). In addition, adding a large amount of Si hardens the material, which reduces the workability of ferritic stainless steel materials.
[0006] Furthermore, as a technique for improving the properties of ferritic stainless steel materials, such as corrosion resistance and temper color resistance, it has been proposed to form an oxide film with concentrated Si on the surface of the ferritic stainless steel material (for example, Patent Documents 4 to 6). Such an oxide film with concentrated Si can be formed by adding Si and performing heat treatment in a BA (bright annealing) atmosphere with a low oxygen concentration. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2018-165384 A [Patent Document 2] JP 2010-229470 A [Patent Document 3] JP 2019-112709 A [Patent Document 4] Japanese Patent Application Publication No. 58-197282 [Patent Document 5] JP 2003-213378 A [Patent Document 6] JP 2008-1945 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, even ferritic stainless steel materials having an oxide film with concentrated Si on the surface cannot be said to have sufficient weather resistance. Regarding the cause of this, a detailed analysis of the oxide film with concentrated Si formed by the conventional method revealed that metal particles such as metallic Fe and metallic Cr with a particle size of several nm were dispersed in the oxide film, and that a Cr-depleted part (hereinafter referred to as "Cr-depleted part") was formed in the surface layer of the material part directly below the metallic particles. This is presumably because the part where abnormal oxidation of the metal occurred in a relatively low temperature range during heat treatment was reduced to metal in a high temperature range. The Cr-depleted part in the surface layer of the material part has low corrosion resistance and does not have a Si-enriched oxide film formed on its surface (metal particles are simply present on the surface), so it is likely to become a corrosion starting point in an outdoor environment, and the desired weather resistance cannot be obtained.
[0009] On the other hand, the Cr-depleted part in the surface layer of the material can be reduced by carrying out a heat treatment for a long time to diffuse Cr to the surface of the material, but carrying out a heat treatment for a long time causes the crystal grains to become coarse and reduces the workability. As described above, in the conventional technology, there was a problem in that it was difficult to achieve both weather resistance and workability in a ferritic stainless steel material having an oxide film with concentrated Si on the surface.
[0010] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a ferritic stainless steel material having excellent weather resistance and workability, and a method for producing the same. [Means for solving the problem]
[0011] The present inventors conducted research focusing on a manufacturing method of ferritic stainless steel material and obtained the following findings. When annealing a ferritic stainless steel material having a predetermined composition in an atmosphere of low oxygen concentration, the generation of the Cr-poor portion itself can be suppressed by increasing the heating rate at 400 to 600°C, where metals such as metallic Fe and metallic Cr (hereinafter referred to as "Cr-poor portion-generating metals") that are the cause of the generation of the Cr-poor portion are likely to be abnormally oxidized (hereinafter referred to as "Cr-poor portion-generating metals"), and shortening the oxidation time. In addition, by controlling the dew point to -60 to -40°C, the abnormal oxidation of the Cr-poor portion-generating metals during heating can be easily suppressed, and the oxidation of Si at temperatures above 600°C can be promoted to form a uniform oxide film in which Si is concentrated. Furthermore, by controlling the heating time at a temperature of 800 to 1000°C to 5.0 minutes or less, the coarsening of crystal grains can be suppressed and workability can be ensured.
[0012] Furthermore, the present inventors analyzed the ferritic stainless steel material obtained as described above and found that the composition and average crystal grain size of the base material, the Si concentration of the oxide film, and the number density of metal formed in the Cr-depleted portion were all within specific ranges. The present invention has been completed based on the above findings.
[0013] That is, the present invention provides a ferritic stainless steel material having a material part and an oxide film formed on the material part, The material portion has a composition, by mass, of C: 0.100% or less, Si: 1.00 to 3.00%, Mn: 1.00% or less, Ni: 1.00% or less, P: 0.100% or less, S: 0.0020% or less, Cr: 13.00 to 32.00%, N: 0.100% or less, a total of Nb and Ti: 6(C+N) to 0.700% (wherein Nb and Ti are each 0.05% or more), Cu: 2.00% or less, Mo: 2.50% or less, with the balance being Fe and impurities, and has an average crystal grain size of 60 μm or less, The oxide film is a ferritic stainless steel material having a Si concentration of 30 mass % or more and a number density of metal generated in Cr-depleted parts of 10 particles / μm or less.
[0014] The present invention also relates to a method for producing a ferritic stainless steel material, the method comprising: heating a ferritic stainless steel material having a composition, by mass, of C: 0.100% or less, Si: 1.00 to 3.00%, Mn: 1.00% or less, Ni: 1.00% or less, P: 0.100% or less, S: 0.0020% or less, Cr: 13.00 to 32.00%, N: 0.100% or less, the total of Nb and Ti: 6(C+N) to 0.700% (wherein Nb and Ti are each 0.05% or more), Cu: 2.00% or less, Mo: 2.50% or less, with the balance being Fe and impurities, in an atmosphere having a dew point of -60 to -40°C and an oxygen concentration of 1.0% by volume or less in a temperature range of 400 to 600°C at a heating rate of 10°C / sec or more, and annealing at a temperature of 800 to 1000°C for 5.0 minutes or less. Effect of the Invention
[0015] According to the present invention, it is possible to provide a ferritic stainless steel material having excellent weather resistance and workability, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The following is a detailed description of the embodiments of the present invention. The present invention is not limited to the following embodiments, and it should be understood that modifications and improvements to the following embodiments, which are made based on the ordinary knowledge of those skilled in the art, fall within the scope of the present invention, without departing from the spirit of the present invention. In this specification, the "%" designation for components means "% by mass" unless otherwise specified.
[0017] A ferritic stainless steel material according to an embodiment of the present invention has a material part and an oxide film formed on the material part. Here, in this specification, the term "stainless steel material" refers to a material formed from stainless steel, and the shape of the material is not particularly limited. Examples of the shape of the material include a plate shape (including a strip shape), a rod shape, a tube shape, and the like. In addition, the material may be various shaped steels having a cross-sectional shape such as a T shape or an I shape. In addition, in this specification, "ferritic" means that the metal structure is mainly ferritic phase at room temperature. Therefore, "ferritic" also includes those that contain small amounts of phases other than ferritic phase (e.g., austenite phase, martensite phase, etc.). However, "ferritic" does not include a multi-phase structure of ferritic phase and austenite phase, a multi-phase structure of ferritic phase and martensite phase, or a multi-phase structure of ferritic phase, austenite phase, and martensite phase.
[0018] The material part has a composition containing C: 0.100% or less, Si: 1.00 to 3.00%, Mn: 1.00% or less, Ni: 1.00% or less, P: 0.100% or less, S: 0.0020% or less, Cr: 13.00 to 32.00%, N: 0.100% or less, the total of Nb and Ti: 6(C+N) to 0.700% (however, Nb and Ti are each 0.05% or more), Cu: 2.00% or less, Mo: 2.50% or less, and the balance being Fe and impurities. In this specification, the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes during industrial production of ferritic stainless steel materials, and are acceptable within a range that does not adversely affect the present invention. For example, impurities include unavoidable impurities. An example of an impurity is O. With regard to the content of each element, "xx% or less" means that the content is xx% or less, but includes an amount exceeding 0% (particularly, exceeding the impurity level).
[0019] If necessary, the material part may further contain one or more selected from Al: 1.00% or less, Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less, REM: 0.100% or less, Ca: 0.100% or less, Sn: 0.100% or less, and B: 0.0100% or less. Each component will be described in detail below.
[0020] (C: 0.100% or less) C is an element that affects the properties of ferritic stainless steel materials (hereinafter sometimes abbreviated as "stainless steel materials"), such as intergranular corrosion resistance (sensitization suppression effect) and workability. In particular, if the C content is too high, the workability and weather resistance of the stainless steel material will decrease. Therefore, the upper limit of the C content is 0.100%, preferably 0.080%, and more preferably 0.050%. On the other hand, the lower limit of the C content is not particularly limited, but an excessively low C content leads to an increase in refining costs. Therefore, the lower limit of the C content is preferably 0.0001%, more preferably 0.0003%, and even more preferably 0.001%.
[0021] (Si: 1.00~3.00%) Silicon is an element effective in improving the properties of stainless steel materials, such as oxidation resistance, mechanical strength, and weather resistance. From the viewpoint of improving weather resistance (e.g., pitting resistance in a neutral environment such as salt water) among these properties, the lower limit of the silicon content is 1.00%, preferably 1.05%, and more preferably 1.10%. On the other hand, if the silicon content is too high, it acts as a solid solution strengthening element, leading to a decrease in workability and a decrease in weld toughness. Therefore, the upper limit of the silicon content is 3.00%, preferably 2.90%, and more preferably 2.80%.
[0022] (Mn:1.00% or less) Mn is an element effective for fixing S (desulfurization). However, if the Mn content is too high, MnS, which is the starting point of corrosion, is easily generated and the ferrite phase is destabilized. Therefore, the upper limit of the Mn content is 1.00%, preferably 0.80%, and more preferably 0.50%. On the other hand, the lower limit of the Mn content is not particularly limited, but from the viewpoint of obtaining the above-mentioned effect of Mn, it is preferably 0.01%, more preferably 0.02%, and even more preferably 0.05%.
[0023] (Ni: 1.00% or less) Ni is an element effective in improving the weather resistance of stainless steel materials, and has the effect of suppressing the progression of pitting corrosion and crevice corrosion in a low pH environment in particular. However, if the Ni content is too high, the ferrite phase becomes unstable and the manufacturing cost increases. Therefore, the upper limit of the Ni content is 1.00%, preferably 0.80%, and more preferably 0.60%. On the other hand, the lower limit of the Ni content is not particularly limited, but from the viewpoint of obtaining the above-mentioned effect, it is preferably 0.01%, more preferably 0.02%, and even more preferably 0.03%.
[0024] (P:0.100% or less) P is an element that affects the properties of stainless steel materials, such as weldability and workability. However, if the P content is too high, the above properties may be deteriorated, so the upper limit of the P content is 0.100%, preferably 0.080%, and more preferably 0.050%. On the other hand, the lower limit of the P content is not particularly limited, but an excessively low P content leads to an increase in refining costs. Therefore, the lower limit of the P content is preferably 0.001%, more preferably 0.005%, and even more preferably 0.008%.
[0025] (S:0.0020% or less) S is an element that generates MnS, which is the starting point of corrosion, and affects the weather resistance and weld toughness of stainless steel materials. In particular, if the S content is too high, the weather resistance decreases, so the upper limit of the S content is 0.0020%, preferably 0.0019%, and more preferably 0.0018%. On the other hand, the lower limit of the S content is not particularly limited, but excessively reducing the S content leads to an increase in refining costs. Therefore, the lower limit of the S content is preferably 0.0001%, and more preferably 0.0002%.
[0026] (Cr:13.00~32.00%) Cr is an element effective in improving the corrosion resistance and oxidation resistance of stainless steel materials. In particular, from the viewpoint of ensuring weather resistance in consideration of outdoor salt damage environments, the lower limit of the Cr content is 13.00%, preferably 14.00%, and more preferably 15.00%. On the other hand, if the Cr content is too high, the manufacturing cost increases and it becomes difficult to ensure the toughness of the hot-rolled material, resulting in a decrease in manufacturability. Therefore, the upper limit of the Cr content is 32.00%, preferably 30.00%, and more preferably 25.00%.
[0027] (N:0.100% or less) N is an element that affects the properties of stainless steel materials, such as intergranular corrosion resistance (sensitization suppression effect) and workability. In particular, if the N content is too high, the weather resistance and workability of the stainless steel material are reduced. Therefore, the upper limit of the N content is 0.100%, preferably 0.080%, and more preferably 0.050%. On the other hand, the lower limit of the N content is not particularly limited, but excessively reducing the N content leads to an increase in refining costs. Therefore, the lower limit of the N content is preferably 0.001%, more preferably 0.003%, and even more preferably 0.005%.
[0028] (Total of Nb and Ti: 6(C+N)~0.700%) Nb and Ti are elements that affect the intergranular corrosion resistance (sensitization suppression effect) of stainless steel materials. In addition, since Nb and Ti are elements that are effective in fixing C and N, the total content of Nb and Ti is determined based on the amount of C and N. That is, the lower limit of the total content of Nb and Ti is 6(C+N)% from the viewpoint of obtaining the above-mentioned effect. However, if the total content of Nb and Ti is too high, in addition to increasing the manufacturing cost, the workability and surface quality of the stainless steel material are deteriorated. Therefore, the upper limit of the total content of Nb and Ti is 0.700%, preferably 0.600%, and more preferably 0.500%. In addition, the individual contents of Nb and Ti are each 0.05% or more, preferably 0.06% or more, from the viewpoint of suppressing the coarsening of crystal grains during annealing. In particular, Nb forms carbonitrides such as NbC and NbN, and the pinning effect of these carbonitrides can effectively suppress the coarsening of crystal grains.
[0029] (Cu:2.00% or less) Cu is an element effective in improving the workability and weather resistance of stainless steel materials. In particular, Cu has the effect of suppressing the progress of pitting corrosion in a low pH environment. However, if the Cu content is too high, the ferrite phase becomes unstable and the manufacturing cost increases. Therefore, the upper limit of the Cu content is 2.00%, preferably 1.50%, and more preferably 1.00%. On the other hand, the lower limit of the Cu content is not particularly limited, but is preferably 0.01%, more preferably 0.02%, and even more preferably 0.03%, from the viewpoint of obtaining the effect of Cu.
[0030] (Mo: 2.50% or less) Mo is an element effective in improving the weather resistance and oxidation resistance of stainless steel materials. In particular, Mo has the effect of suppressing the progress of pitting corrosion in a low pH environment. However, if the Mo content is too high, it leads to a decrease in the workability of the stainless steel material and an increase in the manufacturing cost. Therefore, the upper limit of the Mo content is 2.50%, preferably 2.00%, and more preferably 1.50%. On the other hand, the lower limit of the Mo content is not particularly limited, but from the viewpoint of obtaining the effect of Mo, it is preferably 0.01%, more preferably 0.03%, and even more preferably 0.05%.
[0031] (Al: 1.00% or less, Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less) Al, Zr, Co, V and W are elements effective for improving the oxidation resistance of stainless steel materials. However, if the contents of Al, Zr, Co, V and W are too high, the workability and toughness of the stainless steel materials are reduced, and the manufacturing costs are increased. Therefore, the upper limit of the contents of Al, Zr, Co, V and W is 1.00%, preferably 0.95%, and more preferably 0.90%. On the other hand, the lower limit of the contents of Al, Zr, Co, V and W is not particularly limited, but is preferably 0.001%, and more preferably 0.01%.
[0032] (REM: 0.100% or less, Ca: 0.100% or less) REM and Ca are elements effective for improving the oxidation resistance of stainless steel materials. However, if the REM and Ca contents are too high, it leads to an increase in manufacturing costs. Therefore, the upper limit of the REM and Ca contents is 0.100%, preferably 0.090%, and more preferably 0.080%. On the other hand, the lower limit of the REM and Ca contents is not particularly limited, but is preferably 0.0001%, more preferably 0.0003%, and even more preferably 0.001%. In addition, REM is a general term for Sc, Y, and lanthanoids, a total of 17 elements, and refers to rare earth metals. Specifically, La, Ce, Nd, etc. can be mentioned, and one of these can be contained alone or two or more can be combined. When two or more rare earth elements are contained, the content of the REM refers to the total content of these rare earth elements.
[0033] (Sn:0.100% or less) Sn is an element effective for improving the oxidation resistance of stainless steel materials. However, if the Sn content is too high, Sn segregates and the manufacturability of stainless steel materials decreases. Therefore, the upper limit of the Sn content is 0.100%, preferably 0.090%, and more preferably 0.080%. On the other hand, the lower limit of the Sn content is not particularly limited, but is preferably 0.001%, and more preferably 0.002%.
[0034] (B:0.0100% or less) B is an element effective for improving the secondary workability of stainless steel materials. However, if the B content is too high, the fatigue strength of the stainless steel material decreases. Therefore, the upper limit of the B content is 0.0100%, preferably 0.0090%, and more preferably 0.0080%. On the other hand, the lower limit of the B content is not particularly limited, but is preferably 0.0001%, and more preferably 0.0003%.
[0035] The material portion has an average crystal grain size of 60 μm or less. By controlling the average crystal grain size of the material portion within this range, the workability of the stainless steel material can be ensured. From the viewpoint of stably obtaining this effect, the average crystal grain size of the material portion is preferably 55 μm or less, and more preferably 50 μm or less. On the other hand, the lower limit of the average crystal grain size of the material portion is not particularly limited, but is, for example, 1 μm, preferably 5 μm, and more preferably 10 μm.
[0036] Here, the average grain size of the material can be determined by observing the metal structure of the material with an optical microscope in accordance with JIS G0551:2020. Observation with an optical microscope is performed in accordance with JIS G0551:2020 by drawing straight lines at any position on the optical microscope image, counting the number of intersections between the straight lines and the grain boundaries, and taking the average intercept length as the grain size. The grain size is measured by drawing and measuring 20 or more straight lines in multiple fields of view, and the average value of these is taken as the average grain size.
[0037] Next, the oxide film formed on the material portion will be described. The oxide film is an oxide film in which Si is concentrated, and generally contains SiO2. The oxide film may further contain oxides of metals such as Fe, Cr, and Mn. The oxide film has a Si concentration of 30% or more. By controlling the Si concentration within this range, the barrier properties (weather resistance) of the oxide film can be ensured. From the viewpoint of stably ensuring this effect, the Si concentration of the oxide film is preferably 32% or more, and more preferably 35% or more. On the other hand, the upper limit of the Si concentration of the oxide film is not particularly limited, but is typically 60%.
[0038] Here, the Si concentration of the oxide film can be measured using glow discharge optical emission spectroscopy (GD-OES) in accordance with JIS K0144:2018. Specifically, glow discharge optical emission spectroscopy is used to measure the range from the surface to a depth of 1 μm, and in the obtained component concentration profile in the depth direction, the mass fractions of the elements Si, Fe, Cr, Mn, and Si are obtained at a depth from the maximum value of O (oxygen) to a position where the mass fraction is 1 / 4 of the maximum value. Using the obtained mass fractions of each element, the Si concentration of the oxide film can be calculated by the following formula (1). Si concentration in oxide film [mass%] = Si mass fraction [mass%] / (Fe mass fraction [mass%] + Cr mass fraction [mass%] + Mn mass fraction [mass%] + Si mass fraction [mass%]) × 100 (1)
[0039] The oxide film has a density of metal particles formed in the Cr-depleted portion of 10 particles / μm or less. Here, the term "Cr-poor portion-generating metal" refers to a metal that is a factor in the generation of the Cr-poor portion during annealing in a low-oxygen atmosphere. Examples of the Cr-poor portion-generating metal include metallic Cr and metallic Fe. The term "Cr-poor portion" refers to a portion in which Cr is depleted that is generated in the surface layer of the material portion directly below the metal. By controlling the number density of the metal generated in the Cr-poor portion within the above range, it can be said that the generation of the Cr-poor portion, which serves as the starting point of corrosion, is suppressed in the surface layer of the material portion directly below the metal generated in the Cr-poor portion, and therefore weather resistance can be improved. From the viewpoint of stably securing this effect, the number density of the metal generated in the Cr-poor portion is preferably 9 particles / μm or less.
[0040] The number density of the metal generated in the Cr-poor portion in the oxide film can be determined by preparing a sample by exposing the cross section in the thickness direction of the stainless steel material, and then observing the cross section of the oxide film in the sample with a transmission electron microscope (TEM). Specifically, the number density of the metal generated in the Cr-poor portion can be calculated by dividing the number (pieces) of the metal generated in the Cr-poor portion in this cross section by the observation length (μm) in the direction perpendicular to the thickness direction of the oxide film. The observation length in the direction perpendicular to the thickness direction of the oxide film is 100 μm or more.
[0041] The ferritic stainless steel material according to the embodiment of the present invention can be produced by heating a ferritic stainless steel material having the above composition in an atmosphere with a dew point of -60 to -40°C and an oxygen concentration of 1.0% by volume or less in a temperature range of 400 to 600°C at a heating rate of 10°C / sec or more, and annealing the material at a temperature of 800 to 1000°C for 5.0 minutes or less. The annealing may be bright annealing.
[0042] The ferritic stainless steel material is not particularly limited as long as it has the above composition, but is typically a rolled material. As the rolled material, a hot-rolled material, a cold-rolled material, etc. can be used. The rolled material can be produced according to a method known in the art. For example, the cold-rolled material can be produced by melting a ferritic stainless steel having a predetermined composition, hot rolling, annealing, pickling, and then cold rolling. In addition, the rolled material may be subjected to various treatments (annealing, pickling, polishing, etc.) after rolling.
[0043] The dew point during annealing is −60 to −40° C., preferably −55 to −45° C. By controlling the dew point within this range, abnormal oxidation of metals generated in the Cr-poor portion during heating is easily suppressed, and oxidation of Si is promoted, making it possible to form a desired oxide film. If the dew point is lower than −60° C., the Si concentration in the oxide film is low, making it impossible to obtain the desired weather resistance. If the dew point is higher than −40° C., the number density of metals generated in the Cr-poor portion in the oxide film is high, making it impossible to obtain the desired weather resistance.
[0044] The atmosphere during annealing is a low-oxygen atmosphere with an oxygen concentration of 1.0% by volume or less. The atmosphere may contain an inert gas such as hydrogen gas, nitrogen gas, or argon gas. For example, the atmosphere may be an atmosphere of a single gas of any one of these inert gases, or an atmosphere of a mixed gas of two or more of them. For example, the mixed gas may be a mixed gas containing hydrogen gas and nitrogen gas in a volume ratio of 3:1.
[0045] The heating rate in the temperature range of 400 to 600°C during annealing is 10°C / sec or more, preferably 12°C / sec or more, more preferably 15°C / sec or more. In the temperature range of 400 to 600°C, abnormal oxidation of the metal generated in the Cr-poor portion is likely to occur. Therefore, by setting the heating rate in this temperature range to the above range, abnormal oxidation of the metal generated in the Cr-poor portion can be reduced and the generation of the Cr-poor portion can be suppressed. If the heating rate is less than 10°C / sec, the number density of the metal generated in the Cr-poor portion in the oxide film increases, and the desired weather resistance cannot be obtained. The upper limit of the heating rate is not particularly limited, but is typically 30°C / sec in consideration of the performance of the manufacturing device.
[0046] The heating temperature during annealing is 800 to 1000°C, and the heating time is 5.0 minutes or less. By performing annealing under such conditions, it is possible to suppress the coarsening of crystal grains, and therefore to obtain the desired workability. If the heating temperature exceeds 1000°C and the heating time exceeds 5.0 minutes, the crystal grains become coarse and the workability decreases. Also, if the heating temperature is less than 800°C, the thickness of the oxide film becomes insufficient, and the desired weather resistance cannot be obtained.
[0047] The ferritic stainless steel material according to the embodiment of the present invention produced as described above has excellent weather resistance and workability, and can be used in various applications where these properties are required, such as building materials such as building panels, piping, etc. EXAMPLES
[0048] The present invention will be described in detail below with reference to examples, but the present invention should not be construed as being limited to these.
[0049] A stainless steel having the composition shown in Table 1 (the balance being Fe and impurities) was melted and hot-rolled to obtain a hot-rolled sheet having a thickness of 3.0 mm, and then the hot-rolled sheet was annealed at 1050°C and pickled to obtain a hot-rolled annealed sheet. Next, the hot-rolled annealed sheet was cold-rolled to obtain a cold-rolled sheet having a thickness of 1.0 mm. Next, the cold-rolled sheet was annealed under the conditions shown in Table 2 to obtain a ferritic stainless steel sheet. The heating rate shown in Table 2 means the heating rate in the temperature range of 400 to 600°C. The heating rate during annealing was controlled by adjusting the distance between the cold-rolled sheet and the heating zone. In addition, the atmosphere during annealing was a gas atmosphere with an oxygen concentration of 0.01 volume% or less and a hydrogen gas concentration of 99.9 volume% or more. A sample of 300 mm (rolling direction) x 100 mm (width direction) was cut out from the obtained ferritic stainless steel sheet.
[0050] [Table 1]
[0051] [Table 2]
[0052] The samples obtained above were subjected to the following evaluations.
[0053] (Si concentration in oxide film) A 50 mm square test piece was cut out from the above sample, and the surface was degreased with acetone. Next, a range from the surface of the oxide film to a depth of 1 μm was measured using glow discharge optical emission spectroscopy (GD-OES) in accordance with JIS K0144:2018. The oxide film was analyzed by determining the mass fractions of each of the elements Si, Fe, Cr, Mn, and Si at a depth from the maximum value of the mass fraction of O (oxygen) to a position where it becomes 1 / 4 of the maximum value in the component concentration profile obtained by GD-OES. Then, the Si concentration of the oxide film was calculated by the above formula (1) using the mass fractions of each element obtained.
[0054] (Number density of metals formed in Cr-depleted areas of oxide film) The above sample was cut into 50 mm squares, and then processed with focused ion beam (FIB) at any position to obtain a test specimen with an exposed cross section in the thickness direction. Next, the cross section of the oxide film in the test specimen was observed with a transmission electron microscope (TEM) to measure the number of metals (metal Cr and metal Fe) generated in the Cr-poor portion. The number thus measured was divided by the observation length (μm) in the direction perpendicular to the thickness direction of the oxide film to calculate the number density of the metals generated in the Cr-poor portion. The observation length in the direction perpendicular to the thickness direction of the oxide film was set to 100 μm or more.
[0055] (Average grain size of material) A 10 mm square test piece was cut from the above sample, and then resin was embedded so that the cross section in the rolling direction was the observation surface. Next, the resin-embedded test piece was wet polished to a mirror finish, and then etched with fluoronitric acid to reveal the metal structure, which was then observed under an optical microscope. The observation with the optical microscope was in accordance with JIS G0551:2020, where straight lines were drawn at arbitrary positions on the optical microscope image, the number of intersections between the straight lines and the grain boundaries was counted, and the average intercept length was taken as the grain size. The grain size was measured by drawing and measuring 20 or more straight lines in multiple fields of view, and the average of these was taken as the average grain size.
[0056] (processability) The workability was evaluated by measuring the surface irregularity height (maximum height Rz) after applying strain in a tensile test. The above sample was cut into a size of 200 mm (rolling direction) x 50 mm (width direction), and then a JIS No. 13B test piece was cut out so that the parallel part was in the rolling direction. Next, using this test piece, a 20% strain was applied to the test piece in the longitudinal direction using a tensile tester. The tensile test was performed under conditions of room temperature (25°C) in an air atmosphere and a tensile speed of 200 mm / min. Then, the maximum surface height Rz was measured at the center of the longitudinal direction of the test piece using a contact type roughness measuring instrument (Surfcom 2800 manufactured by Tokyo Seimitsu Co., Ltd.). In this evaluation, a maximum height Rz of 40 μm or less was represented as ○ (good workability), and a maximum height Rz of more than 40 μm was represented as × (poor workability).
[0057] (weather resistance) Weather resistance was evaluated by a salt, dry and wet combined cycle test. A test piece of 100 mm (rolling direction) x 50 mm (width direction) was cut out from the above sample, and three sides of the test piece (except one side in the width direction) were covered with resin (one-liquid condensation type RTV rubber KE44 manufactured by Shin-Etsu Chemical Co., Ltd.). Next, two polyethylene tubes of 20 mmφ x 10 mm were bonded onto a Bakelite plate of 70 mm x 150 mm, and the side of the test piece not covered with resin was placed on top of the tubes and bonded. A salt-dry-wet combined cycle test (CCT) was performed on the measurement sample obtained in this way. The sample was placed in a CCT device so that the surface of the test piece for measurement was at 75° to the horizontal plane and the side of the test piece for measurement not covered with resin was at the bottom, and five cycles were performed, each consisting of 5% salt spray (35°C, 2 hours), drying (60°C, 25% RH, 4 hours), and wetting (50°C, 95% RH, 2 hours). The measurement samples were then washed with water and dried, and the rust area ratio on the surface of the test pieces was evaluated (based on JIS G0595:2004). In this evaluation, if the rating number (RN) is 8.0 or higher (corresponding to a rust area ratio of 0.25% or less), it can be determined that the weather resistance is good.
[0058] The above evaluation results are shown in Table 3.
[0059] [Table 3]
[0060] As shown in Table 3, the ferritic stainless steel sheets of Examples 1 to 6 had good workability and weather resistance because the composition and average crystal grain size of the base material, the Si concentration of the oxide film, and the number density of metal generated in the Cr-depleted part were all within appropriate ranges. In contrast, in the ferritic stainless steel sheet of Comparative Example 1, the heating rate during annealing was too slow, so that the number density of metal generated in the Cr-depleted parts was high and the weather resistance was insufficient. In the ferritic stainless steel sheet of Comparative Example 2, the dew point during annealing was too high, so that the density of metal particles formed in the Cr-depleted portions was high, and the weather resistance was insufficient. In the ferritic stainless steel sheet of Comparative Example 3, the dew point during annealing was too low, so the Si concentration in the oxide film was reduced and the weather resistance was insufficient.
[0061] In the ferritic stainless steel sheet of Comparative Example 4, the heating temperature during annealing was too high, so that the crystal grains became coarse and the average crystal grain size of the material became large, resulting in insufficient workability. In the ferritic stainless steel sheet of Comparative Example 5, the heating time during annealing was too long, so that the crystal grains became coarse and the average crystal grain size of the material became large, resulting in insufficient workability. The ferritic stainless steel sheet of Comparative Example 6 did not contain Nb, and therefore could not obtain the pinning effect of Nb. As a result, the crystal grains became coarse, the average crystal grain size of the material became large, and the workability was insufficient. The ferritic stainless steel sheet of Comparative Example 7 had an excessively low Si content, and therefore the Si concentration in the oxide film was low, resulting in insufficient weather resistance. The ferritic stainless steel sheet of Comparative Example 8 had insufficient weather resistance because the Cr and Ti contents were too low.
[0062] As can be seen from the above results, the present invention can provide a ferritic stainless steel material having excellent weather resistance and workability, and a method for producing the same.
Claims
1. A ferritic stainless steel material having a material portion and an oxide film formed on the material portion, The material portion has a composition including, on a mass basis, C: 0.100% or less, Si: 1.00 to 3.00%, Mn: 1.00% or less, Ni: 1.00% or less, P: 0.100% or less, S: 0.0020% or less, Cr: 13.00 to 32.00%, N: 0.100% or less, a total of Nb and Ti: 6 (C + N) to 0.700% (wherein Nb and Ti are each 0.05% or more), Cu: 2.00% or less, Mo: 2.50% or less, and the balance being Fe and impurities, and an average crystal grain size is 60 μm or less, The oxide film is a ferritic stainless steel material having a Si concentration of 30 mass % or more and a number density of metal particles generated in Cr-depleted portions of 10 particles / μm or less.
2. The ferritic stainless steel material according to claim 1, wherein the material portion further contains, by mass, one or more selected from Al: 1.00% or less, Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less, REM: 0.100% or less, Ca: 0.100% or less, Sn: 0.100% or less, and B: 0.0100% or less.
3. The ferritic stainless steel material according to claim 1 or 2, wherein the Cr-depleted portion-generating metal is metallic Cr and / or metallic Fe.
4. A method for producing a ferritic stainless steel material, the method comprising the steps of: heating a ferritic stainless steel material having a composition, on a mass basis, of 0.100% or less C, 1.00 to 3.00% Si, 1.00% or less Mn, 1.00% or less Ni, 0.100% or less P, 0.0020% or less S, 13.00 to 32.00% Cr, 0.100% or less N, a total of 6(C+N) to 0.700% (wherein Nb and Ti are each 0.05% or more), 2.00% or less Cu, 2.50% or less Mo, with the balance being Fe and impurities, at a temperature rise rate of 10°C / sec or more in an atmosphere having a dew point of -60 to -40°C and an oxygen concentration of 1.0% by volume or less in a temperature range of 400 to 600°C, and annealing the material at a temperature of 800 to 1000°C for 5.0 minutes or less.
5. 5. The method for producing a ferritic stainless steel material according to claim 4, wherein the ferritic stainless steel material further contains, by mass, one or more selected from Al: 1.00% or less, Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less, REM: 0.100% or less, Ca: 0.100% or less, Sn: 0.100% or less, and B: 0.0100% or less.
Citation Information
Patent Citations
Rust-resistant stainless steel and its production
JP1983197282A
Stainless steel annealing-finished material having excellent temper color resistance and production method therefor
JP2003213378A
Bright annealing-finished ferritic stainless steel sheet having excellent rusting resistance and workability and method for producing the same
JP2008001945A
Welded structure made from stainless steel having superior toughness at weld, and stainless steel sheet to be welded
JP2010229470A
Ferritic stainless steel and welded structure
JP2018165384A